Efficiency and Effectiveness Comparative Analysis of Wide Flange Beams and Cellular Beams in A Case Project United Tractor - Essen, Donald; Rahman, Muhammad Nur (Journal of World Conference (JWC), 2020)
United Tractors Company will build a sports center building consist of 3 floors using steel structures. Nowadays, limited land is one of the building development problems. The construction of multi-stored buildings is a solution to the limited land problem. The writer has analyzed beam design with a Wide Flange and Cellular system. Focused on the beam element with construction material in the form of steel with steel quality BJ-37, Fy 240 MPa, Fu 370 MPa. The strength and efficiency of the use of steel tonnage were also analyzed. E-Tabs software 2016 used to steel beam structure analysis. In this beam design planning refers to the steel structure planning following SNI 1729: 2015, SNI 1727: 2013, AISC 2010, ASCE 7-10, and also AISC Design Guide 31. The results of manual verification show that the cross-section of WF 400x200x8x13 and CB 250x125x5x8 with a span length of 6 meters is declared to be strong and safe because fill the strong requirements needs to be smaller than the strength of the plan. The efficiency of the use of Cellular Beam was compared to Wide Flange, the longer of Cellular Beam will increase steel tonnage reductions. The percentage reduction in steel weight will continue to increase when the length of steel usage also increases. This concludes that the use of steel length with steel weight reduction will move linearly. Where in this project with a steel beam length of 1439.27m reduction of steel tonnage was at 19.5%.